Variation of Diagnostic Ultrasound Induced Pulmonary Capillary Hemorrhage with Fraction of Inspired Oxygen - Miller, Douglas L. (Ultrasound Med Biol, 2020)
Pulmonary capillary hemorrhage (PCH) induction by diagnostic ultrasound (DUS) was investigated for the influence of the fraction of inspired oxygen (FiO(2)). Sprague Dawley rats were anesthetized with Telazol Only (TO) or of Telazol plus Xylazine (TX), which can enhance the DUS-PCH. A linear array probe (10L, GE Vivid 7 Dimension) was used in B mode at 7.5 MHz to expose the right lung. FiO(2) of 10%, 20%, 60% and 100% were delivered by a nose cone. The ultrasound images showed the PCH effect as growing comet tail (B-line) artifacts and also revealed subpleural consolidated segments (SCS) for higher FiO(2). PCH for TO with 20% and 60% FiO(2) were significantly greater (P<0.05) than for the 10% FiO(2). PCH for TX with 10% and 20% FiO(2) were significantly greater (P<0.02) than for TO anesthesia. Added xylazine and high % FiO(2) reduced PCH thresholds, but xylazine plus high % FiO(2) together did not lower the PCH threshold further. The lowest threshold observed of 1.4 MPa, corresponding to an in situ Mechanical Index = 0.5.